Phylogenetic Diversity of Lhr Proteins and Biochemical Activities of the Thermococcales aLhr2 DNA/RNA Helicase - Mirna Hajj; Petra Langendijk-Genevaux; Manon Batista; Yves Quentin; Sébastien Laurent; Régine Capeyrou; Ziad Abdel-Razzak; Didier Flament; Hala Chamieh; Gwennaele Fichant; Béatrice Clouet-d’Orval; Marie Bouvier (Biomolecules, 2021)
Helicase proteins are known to use the energy of ATP to unwind nucleic acids and to remodel protein-nucleic acid complexes. They are involved in almost every aspect of DNA and RNA metabolisms and participate in numerous repair mechanisms that maintain cellular integrity. The archaeal Lhr-type proteins are SF2 helicases that are mostly uncharacterized. They have been proposed to be DNA helicases that act in DNA recombination and repair processes in Sulfolobales and Methanothermobacter. In Thermococcales, a protein annotated as an Lhr2 protein was found in the network of proteins involved in RNA metabolism. To investigate this, we performed in-depth phylogenomic analyses to report the classification and taxonomic distribution of Lhr-type proteins in Archaea, and to better understand their relationship with bacterial Lhr. Furthermore, with the goal of envisioning the role(s) of aLhr2 in Thermococcales cells, we deciphered the enzymatic activities of aLhr2 from Thermococcus barophilus (Tbar). We showed that Tbar-aLhr2 is a DNA/RNA helicase with a significant annealing activity that is involved in processes dependent on DNA and RNA transactions.